2012
DOI: 10.1111/j.1476-5381.2011.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential signalling in human cannabinoid CB1 receptors and their splice variants in autaptic hippocampal neurones

Abstract: BACKGROUND AND PURPOSECannabinoids such as D 9 -tetrahydrocannabinol, the major psychoactive component of marijuana and hashish, primarily act via cannabinoid CB1 and CB2 receptors to produce characteristic behavioural effects in humans. Due to the tractability of rodent models for electrophysiological and behavioural studies, most of the studies of cannabinoid receptor action have used rodent cannabinoid receptors. While CB1 receptors are relatively well-conserved among mammals, human CB1 (hCB1) differs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 46 publications
2
40
3
Order By: Relevance
“…To determine whether CRIP 1a over expression would suppress constitutive inhibition of EPSCs by CB 1 Rs, the effects of rimonabant (100 nM) were examined. However, no effect of this inverse agonist was detected regardless of whether CRIP 1a was overexpressed (data not shown), as previously reported for nontransfected hippocampal autaptic cultures (Straiker et al, 2012).…”
Section: Crip 1a Modulates Cb 1 Receptor Signaling and Regulationsupporting
confidence: 68%
“…To determine whether CRIP 1a over expression would suppress constitutive inhibition of EPSCs by CB 1 Rs, the effects of rimonabant (100 nM) were examined. However, no effect of this inverse agonist was detected regardless of whether CRIP 1a was overexpressed (data not shown), as previously reported for nontransfected hippocampal autaptic cultures (Straiker et al, 2012).…”
Section: Crip 1a Modulates Cb 1 Receptor Signaling and Regulationsupporting
confidence: 68%
“…For example, when evaluating the cannabinoid effects on brain-stimulation reward, Fattore et al (2003) showed that the potent non-selective CB 1 /CB 2 receptor agonists WIN55,212-2 and CP 55,940, but not Δ 9 -THC, effectively restored heroin-seeking behavior. In addition, it has been suggested that the signaling of CB 1 receptors may differ between humans and rodents (Straiker et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Although these receptor isoforms seem to exhibit similar pharmacology, they may have different functions in cell physiology. 44 Indeed, the majority of our knowledge of the cannabinoid receptors is in relation to their ligands and receptor binding sites, second messengers or signal transduction mechanisms, and postreceptor intracellular protein-protein interactions. Little, however, is known about regulation of CB1 or CB2 gene expression.…”
Section: Discussionmentioning
confidence: 99%